2013
DOI: 10.13165/st-13-3-2-06
|View full text |Cite
|
Sign up to set email alerts
|

Metacognitive Online Reading Strategies in Foreign Language Learning Context at University

Abstract: Purpose-this research is aimed to identify the metacognitive online reading strategies employed by MRU students and assess the interrelation between online reading strategies and metacognitive awareness. Design/methodology/approach-the authors present and evaluate the findings obtained by using Online Survey of Reading Strategies (OSORS), the survey, which helped to identify MRU students' metacognitive online reading strategies in a foreign language learning context. The methods applied in the research were th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 10 publications
2
7
0
Order By: Relevance
“…However, the participants do not prefer to read newspaper articles, text books, workbooks, and computer-presented reading materials with the percentages of (73%, 68%, 84%, 64%) respectively. Such results align with the findings of previous studies that students like reading short stories but they not reading long texts (Vaiciuniene & Uzpaliene, 2013;Dahish, 2017). The aim of the second part of the questionnaire is to find out the reading strategies that EFL learners deficiencies.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…However, the participants do not prefer to read newspaper articles, text books, workbooks, and computer-presented reading materials with the percentages of (73%, 68%, 84%, 64%) respectively. Such results align with the findings of previous studies that students like reading short stories but they not reading long texts (Vaiciuniene & Uzpaliene, 2013;Dahish, 2017). The aim of the second part of the questionnaire is to find out the reading strategies that EFL learners deficiencies.…”
Section: Discussionsupporting
confidence: 92%
“…This suggests that the readers were engaged not in the reading activity itself but in other aspects such as the story events, the illustrations and visual aspects provided. This is consistent with studies conducted in the United States which found that students prefer short stories and dislike texts with many unfamiliar words (Vaiciuniene & Uzpaliene, 2013;Dahish, 2017). That confirms the association between the two themes referred to previously.…”
Section: Free Readingsupporting
confidence: 90%
See 3 more Smart Citations